2015
DOI: 10.1088/0952-4746/35/4/917
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of creating a positive radiation safety culture in the higher education and research sectors

Abstract: The safety culture of any organisation plays a critical role in setting the tone for both effective delivery of service and high standards of performance. By embedding safety at a cultural level, organisations are able to influence the attitudes and behaviours of stakeholders. To achieve this requires the ongoing commitment of heads of organisations and also individuals to prioritise safety no less than other competing goals (e.g. in universities, recruitment and retention are key) to ensure the protection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…It is, therefore, suggested that a radiation protection curriculum, that covers the topics and the learning outcomes that are recommended for referrers in EU Directive 2014 [ 30 ], is developed, and the number of teaching hours needs to be consistent with the ICRP (2009) recommendations [ 31 ]. Radiation safety training should be an essential part of a university’s commitment [ 33 ]. Appropriate knowledge about radiation dose and protective measures from ionising medical examinations are important components for guideline adherence [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, suggested that a radiation protection curriculum, that covers the topics and the learning outcomes that are recommended for referrers in EU Directive 2014 [ 30 ], is developed, and the number of teaching hours needs to be consistent with the ICRP (2009) recommendations [ 31 ]. Radiation safety training should be an essential part of a university’s commitment [ 33 ]. Appropriate knowledge about radiation dose and protective measures from ionising medical examinations are important components for guideline adherence [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might undermine achievement of potential dose optimisation. However, it is established that on-the-job continuous medical education (CME) in radiation protection was effective and substantially improved radiographers' performance, radiation protection knowledge and skills [29,[34][35][36]. On the other hand, slightly above 50% of the participants were aware that scan protocols are relevant for dose optimisation.…”
Section: Awareness About General Radiation Protection and Dose Optimimentioning
confidence: 99%
“…Such disappointing findings warrant a systematic, comprehensive evaluation of the knowledge of basic radiation protection issues needed for daily practice by students in training (such as medical students, radiography students, and radiology residents), in an attempt to gain insight about the current status of radiation protection education among those who will order, perform or interpret medical imaging examinations in their future professional life. In this perspective, the advantages of creating a positive radiation safety culture in the higher education and research sectors have been outlined, with continuous education and testing for all people involved (including students during their training period) being key to optimise performance, minimise errors, and protect the entire workforce as well as the general public and the environment [13][14][15].…”
Section: Introductionmentioning
confidence: 99%